Space, place and religious landscapes : living mountains - Gunzburg, Darrelyn; Brady, Bernadette (London [England] : Bloomsbury Academic, 2020)
"Exploring sacred mountains around the world, this book examines whether bonding and reverence to a mountain is intrinsic to the mountain, constructed by people, or a mutual encounter. Chapters explore mountains in England, Scotland, Wales, Italy, Ireland, the Himalaya, Japan, Greece, USA, Asia and the Andes, and embrace the union of sky, landscape and people to examine the religious dynamics between human and non-human entities. This book takes as its starting point the fact that mountains physically mediate between land and sky and act as metaphors for bridges from one realm to another, recognising that mountains are relational and that landscapes form personal and group cosmologies. The book fuses ideas of space, place and material religion with cultural environmentalism and takes an interconnected approach to material religio-landscapes. In this way it fills the gap between lived religious traditions, personal reflection, phenomenology, historical context, environmental philosophy, myths and performativity. In defining material religion as active engagement with mountain-forming and humanshaping landscapes, the research and ideas presented here provide theories that are widely applicable to other forms of material religion."--
List of Figures -- List of Maps -- List of Tables -- List of Contributors -- Introduction: Darrelyn Gunzburg and Bernadette Brady (University of Wales Trinity Saint David) Foreword: Professor Christopher Tilley (Professor of Anthropology & Archaeology, UCL) -- PART I: PREHISTORIC CONVERSATIONS -- 1. Frank Prendergast (Technological University, Dublin): The Archaeology of Height-cultural meaning in the relativity of Irish megalithic tomb siting. -- 2. Anna Estaroth (University of Wales Trinity Saint David): How the shadow of the mountains created sacred spaces in Bronze Age Scotland. -- PART 2: MEDIEVAL CONVERSATIONS -- 3. Jon Cannon (University of Bristol): Time and place at Brentor: exploring an encounter with a 'sacred mountain'. -- 4. Darrelyn Gunzburg (University of Wales Trinity Saint David): Building Paradise on the Hill of Hell in Assisi: Mountain as Reliquary. -- PART 3: ANIMISTIC CONVERSATIONS -- 5. Fiona Bowie (Research Affiliate, School of Anthropology and Museum Ethnography, Oxford University): Mountains as sources of power in seen and unseen worlds. -- 6. Amy Whitehead (Massey University, New Zealand): Appalachian animism: religion, the woods, and the material presence of the mountain -- PART 4: STORIED CONVERSATIONS -- 7. Bernadette Brady (University of Wales Trinity Saint David): Mountains talk of kings and dragons, the Brecon Beacons. -- 8. Christos Kakalis (Newcastle University): Representing the Sacred: Printmaking and the depiction of the Holy Mountain. -- PART 5: CONTEMPORARY CONVERSATIONS -- 9. Lionel Obadia (Université de Lyon -- ANR): 'Sacred' Himalayan peaks: for whom? The paradoxical and polylogical construction of mountains. -- 10. Alan Ereira (Professor of Practice, University of Wales, Trinity Saint David): The Black Line of the Sierra Nevada de Santa Marta; a Red Line for a mountain.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Mountains -- Religious aspects; Wilderness (Theology); Material culture; Electronic books